Call to Action for Cardiovascular Disease in Women: Epidemiology, Awareness, Access, and Delivery of Equitable Health Care: A Presidential Advisory From the American Heart Association. Issue 23 (9th May 2022) - Wenger, Nanette K.; Lloyd-Jones, Donald M.; Elkind, Mitchell S.V.; Fonarow, Gregg C.; Warner, John J.; Alger, Heather M.; Cheng, Susan; Kinzy, Claire; Hall, Jennifer L.; Roger, Véronique L.; ,
Abstract : Addressing the pervasive gaps in knowledge and care delivery to reduce sex-based disparities and achieve equity is fundamental to the American Heart Association's commitment to advancing cardiovascular health for all by 2024. This presidential advisory serves as a call to action for the American Heart Association and other stakeholders around the globe to identify and remove barriers to health care access and quality for women. A concise and current summary of existing data across the areas of risk and prevention, access and delivery of equitable care, and awareness and education provides a framework to consider knowledge gaps and research needs critical toward achieving significant progress for the health and well-being of all women.